PENGARUH POLA ASUH ORANG TUA, TEMAN SEBAYA, MEDIA DAN LINGKUNGAN SEKOLAH TERHADAP PERILAKU BULLYING KELAS XI DI SMK AL-WAHYU CIBUBUR TAHUN 2017/2018. - Yuliasari, Rizka; Ambariani, Ambariani; Pujiati, Pujiati (SINERGI : Jurnal Riset Ilmiah, 2025)
Bullying behavior is one of the forms of juvenile delinquency delinquency is malicious behavior (dursila), or crime / juvenile delinquency, is a symptom of social (pathological) pain in children and adolescents caused by a form of social service, so they It develops a form of deviant behavior. Bullying behavior is influenced by several factors including: Parenting parenting, peers, media and school environment. This study aims to determine the influence of parenting parents, peers, media and school environment on the behavior of bullying class XI SMK AL-Wahyu Cibubur 2017/2018 academic year as many as 52 students. The technique used in sampling for this research is proportional random sampling. From the results of data processing with chi-square analysis test showed that positive class XI behaved bullying and had negative parenting effect of 86.2%, who positively behaved bullying and had negative peer influence as much as 82.4% , Who positively behave bullying and have a negative media influence as much as 80.6%, as well as positive behaved bullying and have a negative school environment influence as much as 80.6%. From the statistical results showed a significant relationship between the influence of parenting parents, peers, media and school environment on bullying behavior with p value <0,05. The conclusion of this research is there is influence between parenting parenting, peers, media and school environment to bullying behavior. Therefore, it is expected that the students get the influence of parents' parenting pattern, peers, media and positive school environment so that the students will not become bullying actors.